Occurrence and symptom characterization of Oligonychus grypus Baker & Pritchard (Acari: Tetranychidae) in sugarcane - Ramos, Gabriel; Andrade, Daniel Júnior de (Entomological Communications, 2025)
The occurrence of phytophagous mites in Brazilian sugarcane crops has received limited attention but has increased over the past two decades. Among these mites, Oligonychus grypus Baker & Pritchard, 1960 (Acari: Tetranychidae), commonly known as the African sugarcane mite, is particularly noteworthy. Its populations have intensified, with high-density outbreaks associated with climate change and agricultural practices. In Brazil, this species was first identified in 2009 in the Piracicaba region of São Paulo. Under severe infestations, it causes extensive damage to leaf blades, producing yellowish to whitish spots that indicate its destructive potential. These injuries reduce crop yield and compromise the quality of raw material for industrial processing. This scientific note reports the occurrence of O. grypus in commercial sugarcane fields in the Ribeirão Preto region, São Paulo. It documents the symptoms and potential impacts on the crop, underscoring the importance of monitoring, given the economic significance of sugarcane production in Brazil.